Characterization of Lithium-Ion Battery Thermal Abuse Behavior Using Experimental and Computational Analysis. Issue 10 (1st January 2015) - Lopez, Carlos F.; Jeevarajan, Judith A.; Mukherjee, Partha P.
Abstract : While the popularity of lithium-ion batteries (LIBs) has increased significantly in recent years, safety concerns due to the high thermal instability of LIBs limit their use in applications with zero tolerance for a catastrophic failure. Industries such as aerospace and automotive must be very stringent in their selection and design of lithium-ion cells and modules to meet safety requirements. A safety issue of particular interest is a scenario called thermal runaway in which one or more exothermic side-reactions occur, leading to elevated temperature ranges that in turn lead to an uncontrollable and excessive release of heat. This work aims to characterize the effect of these reactions by utilizing a thermal abuse model that predicts single-cell behavior when subjected to an elevated-temperature. The experimental test of the thermal safety behavior includes a constant-power heating element to trigger a thermal runaway event. This study takes an existing thermal abuse model and modifies it to emulate the conditions during a constant-power heating test. The result is found to be in agreement with the experimental data for different cell configurations. The influence of convection condition, cell physical configuration, and electrolyte combustion on the cell thermal behavior is also investigated.